Factors Associated with Malaria Vaccine Uptake in Sunyani Municipality - Tabiri, D. (My University, 2020)
Introduction: Malaria has and continues to be a major disease of public health concern affecting several million people worldwide. Ghana together with two other countries started a pilot study on a malaria vaccine (RTS,S) envisaged to prevent 4 in 10 malaria cases and 3 in 10 malaria deaths. This study aimed at assessing the factors associated with malaria vaccine uptake in Sunyani Municipality. Methods: The study was a cross-sectional study employing a quantitative approach. A structured questionnaire was administered to parents/caregivers with children eligible to have taken the first three doses of the malaria vaccine by December 2019. Stratified sampling technique was used to select respondents. Ordinal logistic regression analysis was done to determine the association between the independent variables and full vaccine uptake. Results: Uptake of RTS,S 1 was 94.1%. However, this figure reduced to 90.6% for RTS,S 2, and 78.1% for RTS,S 3. Timeliness of uptake was 67.7% for RTS,S 1, 51.9% for RTS,S 2 and 54.7% for RTS,S 3. Children with a parent who had been educated up to the tertiary level had 4.72 [AOR: 4.72, 95%CI: 1.27 – 17.55] increased odds of full uptake as compared to those who completed secondary education. Children with parents who thought vaccines were becoming too many for children had 71% [AOR: 0.29, 95%CI: 0.14 – 0.61] reduced odds of full uptake as compared to those who thought otherwise. Parents whose children had suffered fever as an adverse reaction were more likely to send their kids for the malaria vaccine as compared to those who children had ever suffered abscess as an adverse reaction [AOR: 2.27, 95%CI: 1.13 – 5.10]. Conclusion: Uptake of RTS,S 1 and RTS,S 2 in Sunyani Municipality meets WHO’s target coverage for vaccines, however, RTS,S 3 uptake does not. Furthermore, there is a growing perception amongst parents/caregivers that vaccines are becoming too many for children which negatively affects uptake. The Municipal Health Directorate should therefore put in measures to address this because it has the potential of eroding the gains made through childhood vaccination.
MPH
Keywords: Malaria Vaccine Uptake; Disease; Public health; Ghana; Sunyani Municipality